Identification of Chemical Compounds of Cymbopogon Nardus (L.) Rendle and Ocimum Basilicum (L.) using Gas Chromatography-Mass Spectrometry (GC-MS) - Sari, Eka Syafitri Puspita; Anwar, Yelfi; Maryana, Roni; Muryanto, Muryanto (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
Citronella essential oil (Cymbopogon nardus (L.) and basil leaf essential oil (Ocimum basilicum (L.) offer various benefits, including antibacterial properties. This study aims to identify the chemical compounds present in these oils obtained through local distillation at PT Syailendra Bumi Investama in Wonorejo Village, Gondangrejo, Karanganyar, Central Java. Gas Chromatography-Mass Spectrometry (GC-MS) analysis was conducted at the BRIN (National Innovation Research Agency) in Serpong, South Tangerang, Banten, to characterize citronella essensial oil and basil essential oil. The findings indicate that citronella essential oil meets the criteria of SNI 06-3953-1995, with three compounds showing significant concentrations: Geraniol (26.49%), citronellol (14.53%), and citronellal (10.95%). Similarly, research on basil leaf essential oil conforms to ISO 11043 - 1998 standards, revealing high concentrations of two compounds: Estragole (55.80%) and linalool (22.35%).